APPLIED RESEARCH OF THE RADIAL-RING TYPE OF LEARNING IN THE ACQUISITION OF KNOWLEDGE USING ERGONOMICS (World Bulletin of Social Sciences, 2024)
In this article, an attempt is made to study the quality of the learning process of the radial-ring type of the audience in the acquisition of knowledge, using ergonomic modeling.
Keywords: qualities; research; radial-ring; structural